Relationship between Demographic Characteristics and Ethical Reasoning of Nurses Working in Medical Wards - Firouzeh Safavi; Hossein Ebrahimi; Hossein Namdar Areshtanab; Esmail Khodadadi; Marjaneh Fooladi (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Professional ethics and moral reasoning are among the critical factors influencing professional nursing practice, the quality of patient care, and the patient’s health outcome. Aim: This study aimed to determine the relationship between demographic characteristics of nurses and their ethical reasoning in the medical wards. Materials and Methods: This was a cross-sectional study with descriptive-analytical approach that was conducted in 2016. The study participants consisted of 180 nurses working in the medical wards of hospitals affiliated to Tabriz university of Medical Sciences. The census sampling method was implemented. Data collection tools included a demographic questionnaire and the Nursing Dilemma Test questionnaire (NDT) designed to measure the ethical reasoning among nurses in pre-conventional, conventional and post-conventional levels. Data were analysed by using SPSS version 21.0 with, one-way ANOVA, t-test and Pearson correlation tests. Results: The results indicated that the mean score for ethical reasoning among nurses in medical wards was 45.7±6.1, where nurses scored 37.5%, 35.08%, and 27.42% for preconventional, conventional and post-conventional levels respectively. Researchers found a statistically significant relationship between nurses ethical reasoning and nurses’ shift (p-value <0.05). There were no significant relationships between age, sex, work history and other demographic characteristics, and ethical reasoning scores (p>0.05). Conclusion: Nurse’s ability to accurately identify and manage ethical dilemmas was among the factors that influenced their ethical decision making process. The relationship between nurses’ shift and type of work contributed to the way ethical reasoning was applied. These findings are essential for healthcare administrators to design strategies towards the highest quality nursing care.